Class Warfare: Political Exclusion of the Poor and the Roots of Social-Revolutionary Terrorism, 1860-1950 - Daniel Meierrieks; Tim Krieger; Valentin Klotzbücher (Defence and Peace Economics, 2021)
We examine the effect of class cleavages on terrorist activity by anarchist and leftist terrorist groups in 99 countries over the 1860–1950 period. We find that higher levels of political exclusion of the poor, our main measure of class conflict, were associated with higher levels of social-revolutionary terrorist activity during this time period. This finding is robust to an instrumental-variable approach and further robustness checks. We argue that class cleavages – in the form of the monopolization of political power by the rich – perpetuated and exacerbated the socio-economic ordeal of the poor, while simultaneously curtailing their means to effect relief in the ordinary political process. Consistent with our expectations, this provoked terrorist violence by groups whose ideological orientation highlighted concerns over class conflict, economic equality and the political participation of the poor. Indeed, our empirical analysis also shows that terrorist groups motivated by other ideologies (e.g. extreme nationalism) did not respond to political exclusion of the poor in the same manner, which further emphasizes the role of ideological inclinations in the terrorist response to class antagonisms.
doi:10.17632/rsvkv43b5r.1
Keywords: 300; terrorism; social-revolutionary terrorism; political exclusion of the poor; instrumental-variable approach